Alternative to Tin Ratio Type Estimator - Adewara , A. A. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2015)
In sample surveys, small sample studies are usually known for their sensitivity. Hence, many studies on estimator formulation in ratio estimation are based on moderate or large sample study. In this study, an alternative ratio type estimator capable of solving small sample problems was proposed. The bias and the variance of this alternative ratio type estimator were derived. Two life data sets of small sample sizes and a secondary data of large sample size were used to justify the superiority of the proposed alternative ratio type estimator. It was observed that the proposed alternative ratio type estimator was more efficient than Tin ratio type estimator with respect to its bias and the variance, provided its condition is met.